The lack of value of hepato-jugular reflux as a sign of heart failure. Issue 567 (January 1973) - Singh, S. P.; Haider, R.
Abstract : An investigation was carried out of the diagnostic value of hepato-jugular reflux in patients with heart failure. The effect of abdominal compression on superior vena cava pressure was assessed in patients with and without heart failure. In four of the six patients without congestive cardiac failure, during compression, whether applied in the right hypochondrium or left iliac fossa, there was a significant rise in vena cava pressure. A similar response was also observed in three patients with congestive heart failure. Hepato-jugular reflex is not a reliable sign of incipient heart failure.